Effects of Vitamin D3 Supplementation on the Expression of Interleukin-6 and Vascular Endothelial Growth Factor of Umbilical Cord-Derived Mesenchymal Stem Cells - Ariza Julia Paulina; Elmi Elmi; Nicko Pisceski Kusika Saputra; T Syarifah Dessi IS Assegaf; Dino Irawan; Fadhilla Maulany El Fajri; Maisarah Elfajri Putri; Sucitra Sucitra; Rahma Dhani; Arfianti Arfianti (Fakultas Kedokteran Universitas Riau, 2026)
Mesenchymal stem cells (MSCs) are multipotent stem cells with self-renewal ability, low immunogenicity, homing, and immunomodulatory function; thus, they had great potential in regenerative medicine. Preconditioning of MSCs cultures is known to enhance their immunomodulatory effects in various clinical applications. This study aimed to determine the effect of vitamin D3 supplementation on the viability and expression of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) mRNA in MSCs. Methods: Methods: MSCs were isolated from Wharton's jelly umbilical cord and were cultured using the explant method. MSCs at passage 3 were cultured on 6-well plates and were divided into four experimental groups: 1, 10, and 100 nM vitamin D3 supplementation groups and the control group (without vitamin D3 supplementation). After vitamin D3 supplementation for 24 h, viability was examined using the Cell Counting Kit 8 (CCK 8) assay, and IL-6 and VEGF mRNA expression was analyzed using quantitative polymerase chain reaction (qPCR). Data were analyzed using one-way ANOVA, and p-value < 0.05 was considered significant. Results: MSCs supplemented with vitamin D3 at concentrations of 1, 10, and 100 nM for 24 h showed increased viability. Findings indicated that supplementation with vitamin D3 1 nM for 24 h significantly decreased IL-6 expression, whereas supplementation of vitamin D3 10 and 100 nM for 24 h increased IL-6 expression compared to the control group, but the difference were not significant (p=0.1883). Supplementation with vitamin D3 at 10 nM for 24 h significantly decreased VEGF expression compared to that in the control group. Vitamin D3 preconditioning modulated IL-6 and VEGF mRNA expression in UC-MSCs, suggesting potential effects on inflammatory and angiogenic pathways. Conclusion: Vitamin D3 supplementation modulated IL-6 and VEGF expression in UC-MSCs in a dose-dependent, non-linear manner.